2021
DOI: 10.1108/jabs-10-2020-0423
|View full text |Cite
|
Sign up to set email alerts
|

The power to voice my hate! Exploring the effect of brand hate and perceived social media power on negative eWOM

Abstract: Purpose Consumer brand relationship literature has recently seen a surge of studies on brand hate, its antecedents and outcomes. Hate alone will not drive consumers to engage in negative electronic word-of-mouth (eWOM) and indicates the interplay of other social relationship factors that can strengthen the effect of brand hate on negative eWOM. The purpose of this study is to integrate the emerging concept of brand hate and perceived social media power with the theory of planned behavior (TPB) to expand the un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(8 citation statements)
references
References 129 publications
(226 reference statements)
0
8
0
Order By: Relevance
“…Sharing negative words of mouth is also considered as a consumer voice against brands to communicate their negative experiences, attitudes, and emotions including brand hate. A recent research study on Indian consumers also found negative words of mouth as a strong means to express their voice as a consequence of brand hate ( Sharma et al, 2021 ). Moreover, the research study also found that negative consumer emotions based on perceptions of unfairness and injustice led to consumer retaliation ( Grégoire and Fisher, 2008 ; Zhang et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…Sharing negative words of mouth is also considered as a consumer voice against brands to communicate their negative experiences, attitudes, and emotions including brand hate. A recent research study on Indian consumers also found negative words of mouth as a strong means to express their voice as a consequence of brand hate ( Sharma et al, 2021 ). Moreover, the research study also found that negative consumer emotions based on perceptions of unfairness and injustice led to consumer retaliation ( Grégoire and Fisher, 2008 ; Zhang et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…The above relationship has been tested by Sharma et al (2021). As brand hate is a relatively new topic, interesting dimensions, antecedents, and consequences are still being explored.…”
Section: Brand Hatementioning
confidence: 99%
“…As Table 6 presents, Brand attitude is explored the most. It is found that attitude toward brand leads to eWOM (Sharma et al, 2021). Various facilitators mediate the mentioned relationship, such as brand hate (Sharma et al, 2021), and so forth.…”
Section: Ado Frameworkmentioning
confidence: 99%
See 1 more Smart Citation
“…These individuals attach heightened importance to the impression they present to others (Eisingerich et al, 2015; Sedikides & Strube, 1995), and thus, they are more likely to remain vigilant and react more negatively toward a brand's behavior if they perceive it as potentially damaging to their self‐image. The amplifying effect of high SBC on felt betrayal would consequently cause a decline in consumer attitudes and purchase intentions (predictor of actual purchasing behavior; Morrison, 1979), and lead consumers to engage in negative word of mouth (WOM) (Sharma et al, 2022; Wangenheim, 2005). Negative WOM is an active consumer reaction which influences other people's attitudes (e.g., Bone, 1995; Weitzl et al, 2018), decisions (Wangenheim & Bayón, 2004), and purchase intentions (Herr et al, 1991).…”
Section: Conceptual Developmentmentioning
confidence: 99%